A Method for Memory Integrity Authentication Based on Bloom Filter. Issue 3 (September 2014) - Nianmin, Yao; Haifeng, Ma; Yong, Han
Secure processor architectures can provide secure computing environments. All kinds of applications that need high security should be immune to both physical and software attacks through the secure architectures. Memory integrity verification is a key problem while implementing secure processors. This paper proposed a scheme called IV-BF to ensure data integrity. The scheme is one-level hash structure, and it has three advantages over existing mainstream hash tree based schemes: lower computation overhead, lower space overhead and adjustable level of security. This paper evaluated the overhead and the security of IV-BF and compared it with an efficient integrity checking scheme-BMT. The evaluation result shows that for most benchmarks, the overhead of the IV-BF is lower and the IV-BF has 1%–7% performance improvement than the BMT.